Pseudochromis yamasakii, new species of dottyback fish from Japan (Teleostei: Pseudochromidae: Pseudochrominae) - Gill, Anthony C.; Senou, Hiroshi (Zootaxa, 2016)
Gill (2004) recognised fifty-seven species in the Indo-Pacific genus Pseudochromis Rüppell (1835) but noted that the genus is undiagnosed cladistically and effectively serves as a catch-all for species that can’t be placed in other pseudochromine genera (sensu Gill 2013). Since publication of Gill’s revision, 13 additional species of Pseudochromis have been described, mostly based on recent collections from the highly diverse Coral Triangle area of the West Pacific (Gill & Allen 2004, 2011; Allen et al. 2008; Gill et al. 2009, 2012a,b; Gill & Williams 2011; Gill & Zajonz 2011; Allen & Erdmann 2012). We herein describe an additional new species, which is known on the basis of a single specimen from Kii Peninsula, Honshu, Japan, and from several photographs from the Kii Peninsula and Izu Islands, Japan.